Business Model Innovation for Local Energy Management: A Perspective from Swiss Utilities - Facchinetti, Emanuele; Eid, Cherrelle; Bollinger, Andrew; Sulzer, Sabine (Frontiers in Energy Research, 2016)
The successful deployment of the energy transition relies on a deep reorganization of the energy market. Business model innovation is recognized as a key driver of this process. This work contributes to this topic by providing to potential Local Energy Management stakeholders and policy makers a conceptual framework guiding the Local Energy Management business model innovation. The main determinants characterizing Local Energy Management concepts and impacting its business model innovation are identified through literature reviews on distributed generation typologies and customer/investor preferences related to new business opportunities emerging with the energy transition. Afterwards, the relation between the identified determinants and the Local Energy Management business model solution space is analyzed based on semi-structured interviews with managers of Swiss utilities companies. The collected managers’ preferences serve as explorative indicators supporting the business model innovation process and provide insights to policy makers on challenges and opportunities related to Local Energy Management.